Improving Entrepreneurial Spirit Through Business Plan In Manunggal Village, Deli Serdang - Putra, Muhammad Umar Maya; Sinto, Sinto; Chan, Syafri; Panjaitan, Tuah; Nasution, Asmara Sari (International Journal of Multidisciplinary Sciences and Arts, 2024)
This Community Partnership Service is a concept of applying entrepreneurship courses in the Entrepreneurship Management Study Program at the Faculty of Economics, Universitas Al Azhar based on the Community Empowerment Program, it is expected that the Management Study Program will know the importance of entrepreneurship in improving business and continue to the community in Manunggal Village, Deli Serdang Regency. The method that will be used is the experimental learning method and the concept of literature study on entrepreneurship and SWOT Analysis. The delivery is in the form of lectures, group discussions so that people can actively participate in this activity. In the training, the material presented: The concept of entrepreneurship. After the activity was carried out, it was found that the participants were quite responsive and enthusiastic in following the training material, as evidenced by the many questions asked by the participants and there was a business plan made to make it after the next Batch series at Universitas Al Azhar